General perception of public servants on the realization of Malaysian’s Vision 2020: a case study at Jabatan Ketua Menteri Melaka / Mohd Zulfadhli Zakaria and Amir Mahmud Mohd Musthafa - Zakaria, Mohd Zulfadhli; Mohd Musthafa, Amir Mahmud (Faculty of Administrative Science and Policy Studies, 2013)
This study seeks to determine the public servants general perceptions towards the realization of Malaysia’s Vision 2020 in Jabatan Ketua Menteri Melaka. There are two possible aspects that might influence the general perception on the realization of Malaysian’s Vision 2020. A sample size of 136 had been selected and the data were gathered through questionnaire. The findings showed that there are significant relationships between the two possible conditions that influence the general perception. A significant relationship between general perceptions and economic conditions showed that economic conditions affects in shaping public servants general perceptions. A significant relationship between general perceptions and social conditions showed that social conditions have more effects in shaping public servants general perceptions. Besides, social conditions are most significant condition that shaped public servants general perception towards the realization of Malaysian’s Vision 2020. In conclusion, there are relationships between social and economic conditions towards general perception of public servants that perceive Malaysia can achieve Vision 2020. Hence, public servants in Jabatan Ketua Menteri Melaka perceive that Malaysia can achieve Vision 2020